Laboratory of modernity : Ukraine between empire and nation, 1772-1914 - Bilenʹkyĭ, Serhiĭ (Monograph series (Peter Jacyk Centre for Ukrainian Historical Research), 2023)
"When the powers of Europe were at their prime, present-day Ukraine was divided between the Austrian and Russian empires, each imposing different political, social, and cultural models on its subjects. This inevitably led to great diversity in the lives of its inhabitants, shaping modern Ukraine into the multiethnic country it is today. Making innovative use of methods of social and cultural history, gender studies, literary theory, and sociology, Laboratory of Modernity explores the history of Ukraine throughout the long nineteenth century and offers a unique study of its pluralistic society, culture, and political scene. Despite being subjected to different and conflicting power models during the nineteenth and early twentieth centuries, Ukraine was not only imagined as a distinct entity with a unique culture and history but was also realized as a set of social and political institutions. The story of modern Ukraine is geopolitically complex, encompassing the historical narratives of several major communities--including ethnic Ukrainians, Poles, Jews, and Russians--who for centuries lived side by side. The first comprehensive study of nineteenth-century Ukraine in English, Laboratory of Modernity traces the historical origins of some of the most pressing issues facing Ukraine and the international community today."--